2021
DOI: 10.1038/s41598-021-96752-3
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclones shape mangrove productivity gradients in the Indian subcontinent

Abstract: Recent literature on the impact of cyclones on mangrove forest productivity indicates that nutrient fertilizations aided by tropical cyclones enhance the productivity of mangrove forests. We probe the implications of these predictions in the context of Indian mangroves to propose potential future directions for mangrove research in the subcontinent. First, we look at the time series trend (2000–2020) in satellite-derived gross primary productivity (GPP) datasets for seven mangrove forests across the country’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…where 0.04 is plot size in hectare and 25 is a constant used to extrapolate the measurement of the basal area from per plot (m 2 /plot) to per hectare (m 2 /ha). The Species Diversity index, determined in this study using the Shannon-Wiener's Index [25], indicated a quantitative description of mangrove habitat in terms of species distribution and evenness; this species diversity index was used in several studies [26][27][28] and was calculated using the following form: H = − ∑ P i lnP i (7) where: H = the value of the Shannon-Wiener diversity index Pi = the proportion of ith species individuals to total species individuals ln = the natural logarithm of P i Evenness Index, E = H /ln(S) (8) where, S = Number of species in the study area…”
Section: Species Composition and Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…where 0.04 is plot size in hectare and 25 is a constant used to extrapolate the measurement of the basal area from per plot (m 2 /plot) to per hectare (m 2 /ha). The Species Diversity index, determined in this study using the Shannon-Wiener's Index [25], indicated a quantitative description of mangrove habitat in terms of species distribution and evenness; this species diversity index was used in several studies [26][27][28] and was calculated using the following form: H = − ∑ P i lnP i (7) where: H = the value of the Shannon-Wiener diversity index Pi = the proportion of ith species individuals to total species individuals ln = the natural logarithm of P i Evenness Index, E = H /ln(S) (8) where, S = Number of species in the study area…”
Section: Species Composition and Diversitymentioning
confidence: 99%
“…Therefore, Shannon-Wiener's diversity index (H ) value of the mangrove community of LetKhutKon Village was very low compared to other natural mangrove forests since the mangrove stand in the study site possessed a low number of mangrove species and was dominated by the few species. In contrast to tropical lowland rainforest, the mangroves have very low diversity as few plants have their special adaptations, which are attributed to their unique stands formation and harsh coastal habitat [8].…”
Section: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We found an approximate three-year recovery period, which is in agreement with [36] but differs from others (Table 1). Tropical cyclones can enhance mangrove forest growth by delivering nutrient-rich sediments [56] and soil accretion [57] which can aid in faster recovery. However, frequent cyclones can compound the recovery period of a single disaster event (e.g., Rashmi and Aila struck within three years of Sidr) (Table S1).…”
Section: Post-sidr Recovery and Long-term Vegetation Dynamicsmentioning
confidence: 99%
“…Mangrove forests are some of the most productive coastal ecosystems on the planet. They are found to sequester more carbon than their territorial counterparts and can reduce erosion and ooding risks during storms (Alongi, 2011;Rasquinha and Mishra, 2021). Apart from these important climate regulating services, they are also valued for their provisioning ( sh, fuelwood, materials), supporting (nutrient cycling, photosynthesis, and carbon assimilation, and refugia functions), and cultural services (recreational, religious, spiritual, aesthetic, educational and sense of place) across the globe (Walters et al, 2008).…”
Section: Introductionmentioning
confidence: 99%